An Innovative Technique for Biometric Recognition of Face and Palm-Print Multimodal using Matching Level Fusion - Madhuri M. Barhate (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This paper gives a innovative method for the Recognition of Face and Palm-Print. Main motive of this paper is ti increase robustness of the recognition systems. Traits are combined with different biometric fusion techniques and results are very innovative. Fusion technique can be implemented by two approaches, Combination like wavelet transformation, HOG, DCT, etc. and Classification like k-Nearest Neighbors (kNN), Random Forest, etc. Biometric fusion was implemented on matching score level. Database used for experiments were, faces94, faces95, faces96 and IITD Palmprint Database using various Face recognition and Palm recognition algorithms. Results of which are discussed further in the paper.